2023
DOI: 10.1039/d3en00429e
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the long-term behaviour of nZVI and biochar in metal(loid)-contaminated soil: focus on Fe transformations

Aikaterini Mitzia,
Martina Vítková,
Gildas Ratié
et al.

Abstract: The long-term behaviour of stabilising amendments for soil remediation is rarely being tested. Therefore, we conducted time-dependent experiments using contaminated soil from a post-mining area. The soil was individually incubated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 103 publications
(198 reference statements)
0
1
0
Order By: Relevance
“…Consequently, previously sorbed metal(loid)s may be released, increasing their leaching over time (Danila et al, 2020). Nonetheless, it had been reported that nZVI oxidation is not directly proportional to time and the coexistence of poorly crystalline (i.e., ferrihydrite) and more crystalline (i.e., magnetite, lepidocrocite, goethite) Fe (oxyhydr)oxides is possible (Mitzia et al, 2023). The additional reaction mechanism between S-nZVI and metal (loid)s involves sulfide formation, i.e., the substitution of Fe in FeS to form metal(loid) sulfides, which are very stable implying that the immobilized metal(loid)s are not likely to be released into solution again.…”
Section: Metal Bioavailability In the Treated Soilsmentioning
confidence: 99%
“…Consequently, previously sorbed metal(loid)s may be released, increasing their leaching over time (Danila et al, 2020). Nonetheless, it had been reported that nZVI oxidation is not directly proportional to time and the coexistence of poorly crystalline (i.e., ferrihydrite) and more crystalline (i.e., magnetite, lepidocrocite, goethite) Fe (oxyhydr)oxides is possible (Mitzia et al, 2023). The additional reaction mechanism between S-nZVI and metal (loid)s involves sulfide formation, i.e., the substitution of Fe in FeS to form metal(loid) sulfides, which are very stable implying that the immobilized metal(loid)s are not likely to be released into solution again.…”
Section: Metal Bioavailability In the Treated Soilsmentioning
confidence: 99%